Multistaged discharge constructing heterostructure with enhanced solid-solution behavior for long-life lithium-oxygen batteries - Shu-Mao Xu (Nature Portfolio, 2019)
Li–O2 batteries suffer from poor charge transport in the insulating discharge products. Here the authors tackle the issue by pre-depositing a K2CO3 layer and then using this to grow Li2O2 film on top, enabling enhanced electronic conduction properties and improved overall performance.